2016
DOI: 10.1177/183693911604100311
|View full text |Cite
|
Sign up to set email alerts
|

Social Inclusion and Exclusion of a Young Child: A Cultural–historical Perspective of an International Mid-semester Transition into an International School in Malaysia

Abstract: EXPATRIATE CHILDREN POTENTIALLY experience multiple international transitions in their early childhood years as their parents move countries to fulfill the demands of employment with multinational companies. However, we know very little about the social interaction that occurs as young expatriate children enter into international schools. The focus here is the processes of a mid-semester transition, which resulted in both inclusion and exclusion practices. These processes are explored using Vygotsky's (1994) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
5
0
2
Order By: Relevance
“…Previously, TCK experiences have been analyzed from a variety of perspectives, including childhood adjustment (Banerjee et al, 2020;De Sivatte et al, 2019;Weeks et al, 2010) and coping (Van der Zee et al, 2007) abroad. Further studies have focused on how expatriate children establish relationships during international transitions (Adams, 2016;Lijadi and Van Schalkwyk, 2014). Research conducted on globally mobile children has also covered their perceptions of being international (Lam and Selmer, 2004;Selmer and Lam, 2004), their international mindedness (Poonoosamy, 2018), global awareness (Sheard, 2008), their sense of belonging to the home country (Nette and Hayden, 2007) and adolescents' stress reactivity and depressive symptoms (Thomas et al, 2021); and scholars have shown interest in TCKs' future career interests when they are still young (Gerner and Perry, 2000;Lam and Selmer, 2004;Selmer and Lam, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, TCK experiences have been analyzed from a variety of perspectives, including childhood adjustment (Banerjee et al, 2020;De Sivatte et al, 2019;Weeks et al, 2010) and coping (Van der Zee et al, 2007) abroad. Further studies have focused on how expatriate children establish relationships during international transitions (Adams, 2016;Lijadi and Van Schalkwyk, 2014). Research conducted on globally mobile children has also covered their perceptions of being international (Lam and Selmer, 2004;Selmer and Lam, 2004), their international mindedness (Poonoosamy, 2018), global awareness (Sheard, 2008), their sense of belonging to the home country (Nette and Hayden, 2007) and adolescents' stress reactivity and depressive symptoms (Thomas et al, 2021); and scholars have shown interest in TCKs' future career interests when they are still young (Gerner and Perry, 2000;Lam and Selmer, 2004;Selmer and Lam, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…, 2007) abroad. Further studies have focused on how expatriate children establish relationships during international transitions (Adams, 2016; Lijadi and Van Schalkwyk, 2014). Research conducted on globally mobile children has also covered their perceptions of being international (Lam and Selmer, 2004; Selmer and Lam, 2004), their international mindedness (Poonoosamy, 2018), global awareness (Sheard, 2008), their sense of belonging to the home country (Nette and Hayden, 2007) and adolescents' stress reactivity and depressive symptoms (Thomas et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Eight studies used a multi-informant perspective. It is important to note that of these, four papers came from one study conducted in Malaysia (Adams, 2014;Adams & Fleer, 2015;Adams, 2016;Adams & Fleer, 2016). Similarly, two papers came from one study conducted in England (McLachlan, 2007;.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Even though there is a longstanding tendency for migrant or mobile persons to move away from Switzerland in the shorter or longer term 2 , there is an increasing number of families moving to Switzerland as part of a trajectory of repeated mobility. Typically, one would expect such families to send their children to international schools (Adams and Fleer 2016;Gyger Gaspoz 2013;Pearce 2013). Surprisingly, the migration-mobility survey conducted in Switzerland in 2015 suggested that 75% of families with an experience of repeated mobility 3 send their children to public schools (Levitan 2018).…”
Section: Children In Repeated Mobility In Public Swiss Schoolsmentioning
confidence: 99%